Revolutionizing microfinance: a blockchain-driven decentralized finance (DeFi) model for collateral-free loans - Tasin, Md. Ishmam; Hossain, Md. Rabib; Chowdhury, Nahin; Alam, S.M. Azwad-Ul- (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.